2013
DOI: 10.1016/j.jprot.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The “Vampirome”: Transcriptome and proteome analysis of the principal and accessory submaxillary glands of the vampire bat Desmodus rotundus, a vector of human rabies

Abstract: Vampire bats are notorious for being the sole mammals that strictly feed on fresh blood for their survival. While their saliva has been historically associated with anticoagulants, only one antihemostatic (plasminogen activator) has been molecularly and functionally characterized. Here, RNAs from both principal submandibular and accessory glands of Desmodus rotundus were extracted, and ~ 200 million reads were sequenced by Illumina. The principal gland was enriched with plasminogen activators with fibrinolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 138 publications
1
43
0
Order By: Relevance
“…More recently, the first transcriptome analysis of the principal submaxillary gland of D. rotundus was reported. 22 This extensive database identified-among several genes-1 candidate member of the Kunitz family of proteins that was annotated as an anticoagulant based on its similarity to TFPI. 0, 62, 125, 250, 500, and 1000 nM) in 20 mM Tris, 0.15 M NaCl, 0.3% bovine serum albumin, pH 7.4, for 10 minutes at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the first transcriptome analysis of the principal submaxillary gland of D. rotundus was reported. 22 This extensive database identified-among several genes-1 candidate member of the Kunitz family of proteins that was annotated as an anticoagulant based on its similarity to TFPI. 0, 62, 125, 250, 500, and 1000 nM) in 20 mM Tris, 0.15 M NaCl, 0.3% bovine serum albumin, pH 7.4, for 10 minutes at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this marked effect in the aPTT has been observed before with vampire bat saliva, suggesting that Desmolaris accounts for this activity in nature. 19 Whether other molecules identified in the transcriptome analysis of the gland 22 contribute to the anticoagulant activity of saliva remains to be determined. Experiments also demonstrated that inhibition of FXIa by Desmolaris was enhanced 12 times by heparin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo assembly of millions/billions of RNA-Seq reads into a reference transcriptome can provide a valuable scientific resource, with applications in phylogenetics 36 , novel gene identification 37 , RNA editing 38 and alternative splicing investigation 39 , qPCR primer design 40 , development and refinement of bioinformatics software 41 , augmenting proteomic research 42 , and investigation of gene expression profiles underlying complex physiological traits 43,44 . The utility of a transcriptome assembly is highly dependent on its completeness and accuracy, however there is not yet consensus within the transcriptomics community on a universal 'gold-standard' protocol or quality metric for transcriptome assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The protein sequences were aligned by the ClustalX software program. The phylogenetic tree was created with the Mega package after 10,000 bootstraps with the neighbor-joining algorithm, using the p-dis-tance model as described (6,29). The bar at the bottom of each tree represents 10% amino acid substitution.…”
Section: Methodsmentioning
confidence: 99%